WEBSITE NETWORK AUTOMATION DESIGN AND IMPLEMENTATION IN RT RW NET SENDEN DUSUN MAGELANG WITH DJANGO FRAMEWORK - Yoel Chandra Eka Paksi; Indrastanti R. Widiasari (Jurnal Teknik Informatika (Jutif), 2022)
RT RW NET is part of the Internet facilities owned by the hamlet of Senden Magelang, whose purpose is to provide cheap Internet facilities.However, behind the existing facilities several problems emerged, based on a statement from the hamlet of sending that the problem that arose was the configuration process for adding new users, which took a long time due to manual configuration in each RT (Rukun Tetangga) and RW (Rukun Warga) alley. Therefore, in this study, a website-based network automation application was created using the Django framework and developed using the Waterfall method, thus providing easy access and fast configuration when configuring new users. After designing the network automation website, the website will be operated by the network administrator, who hopes to simplify and shorten the time for new user configurations.